2015
DOI: 10.1016/j.jgr.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Korean Red Ginseng attenuates ethanol-induced steatosis and oxidative stress via AMPK/Sirt1 activation

Abstract: BackgroundAlcoholic steatosis is the earliest and most common liver disease, and may precede the onset of more severe forms of liver injury.MethodsThe effect of Korean Red Ginseng extract (RGE) was tested in two murine models of ethanol (EtOH)-feeding and EtOH-treated hepatocytes.ResultsBlood biochemistry analysis demonstrated that RGE treatment improved liver function. Histopathology and measurement of hepatic triglyceride content verified the ability of RGE to inhibit fat accumulation. Consistent with this, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…Chronic alcohol exposure impairs adenosine monophosphate‐activated protein kinase (AMPK)/sirtuin 1 (Sirt1) axis, which is involved in regulating energy metabolism (You, Liang, Ajmo, & Ness, ; You, Matsumoto, Pacold, Cho, & Crabb, ) Ginsenoside Rb2 and Rd supplementation inhibited fat accumulation induced by ethanol. Accordingly, Rb2 and Rd effectively rescued ethanol‐induced suppression of Sirt1 and PPARα (Han et al, ).…”
Section: Natural Compounds Beneficial For Ald Treatmentmentioning
confidence: 99%
“…Chronic alcohol exposure impairs adenosine monophosphate‐activated protein kinase (AMPK)/sirtuin 1 (Sirt1) axis, which is involved in regulating energy metabolism (You, Liang, Ajmo, & Ness, ; You, Matsumoto, Pacold, Cho, & Crabb, ) Ginsenoside Rb2 and Rd supplementation inhibited fat accumulation induced by ethanol. Accordingly, Rb2 and Rd effectively rescued ethanol‐induced suppression of Sirt1 and PPARα (Han et al, ).…”
Section: Natural Compounds Beneficial For Ald Treatmentmentioning
confidence: 99%
“…Inhibition of hsp90 by 17-dimethylamino-ethylamino-17-demethoxygeldanamycin ameliorated the steatosis and liver inflammation induced by chronic-plus-binge ethanol feeding, which suggests that hsp90 is a promising therapeutic target for the treatment of ALD 96 . More recently, the chronic-plus-binge ethanol feeding model has also been used to test the therapeutic potential of many drugs/compounds, including a CB2 agonist 62 , betulin (a triterpene from the bark of Betula platyphylla Suk) 97 , luteolin (a flavonoid) 98 , Lactobacillus rhamnosus GG 99 , Korean Red Ginseng 100 , glycycoumarin (a representative coumarin from traditional Chinese Medicine licorice) 101 , flaxseed oil enriched in α-linolenic acid (a plant-derived n-3 polyunsaturated fatty acid) 102 , thymoquinone (a biologically active compound isolated from the seeds of Nigella sativa L.) 103 , and β-caryophyllene (BCP: a plant-derived FDA-approved food additive with anti-inflammatory properties) 104 . The data from these studies revealed that treatment with all of these components ameliorated the chronic-plus-binge alcohol-induced liver inflammation and steatosis in mice.…”
Section: Application Of Chronic-plus-binge Ethanol Model In Testing Tmentioning
confidence: 99%
“…Red ginseng extract improves chronic alcohol-induced histopathological changes of liver in mice. This extract also inhibits oxidative stress and lipid peroxidation by reducing the formation of 4-HNE and the number of 4-HNE-positive cells and protects hepatocytes from inflammation and necrosis by activating AMP-activated protein kinase (AMPK)/Sirt1 pathway [82]. Recently, black ginseng extract has been reported to maintain the cellular redox status by restoring NOX and GSH level change and alleviate oxidative stress by reducing intracellular ROS production and lipid peroxide 4-HNE signals, resulting in the protection of hydrogen peroxide-induced oxidative damage in AML-12 cells [83].…”
Section: Protection Against Liver Injurymentioning
confidence: 99%